Niemann-Pick disease type C clinical database: cognitive and coordination deficits are early disease indicators - Stampfer, Miriam; Theiß, Susanne; Amraoui, Yasmina; Jiang, Xuntian; Keller, Sigrid; Ory, Daniel S.; Mengel, Eugen; Fischer, Christine; Runz, Heiko (Orphanet journal of rare diseases, 2013)
The neurodegenerative lysosomal storage disorder Niemann-Pick disease type C (NP-C) is characterized by a broad clinical variability involving neurological, psychiatric and systemic signs. Diverse patterns of disease manifestation and progression considerably delay its diagnosis. Here we introduce the NP-C clinical database (NPC-cdb) to systematically obtain, store and analyze diagnostic and clinical findings in patients with NP-C. We apply NPC-cdb to study NP-C temporal expression in a large German-Swiss patient cohort.
Gesehen am 15.02.2022